Inclusion in Action: Fostering Empathy and Creativity with the CYBATHLON@school Contest (Constructionism Conference Proceedings, 2025)
The CYBATHLON @school Program, part of the CYBATHLON initiative, integrates STEM education with empathy-building by engaging students in creating prototypes of assistive technologies for individuals with disabilities. The CYBATHLON @school Contest invited school classes to tackle the challenges faced by real or hypothetical individuals with disabilities through design thinking and prototyping, fostering creativity and empathy. More than 300 students from 16 classes (Grades 4 to 9) submitted 125 posters showcasing their innovative solutions. Winning teams earned makerspace access and public recognition during the CYBATHLON 2024 competition. This poster presents the contest structure, materials, and early insights from student projects, offering a possible role model for combining STEM education with inclusion and creativity.